Inequalities in the dental treatment provided to children: an example from the UK - Tickle M, Milsom KM, Blinkhorn AS. (Blackwell Synergy, 2002)
To identify the relationship between the socioeconomic status of frequently attending children and the dental care of their primary dentition provided by dentists working in the General Dental Service (GDS) of the UK National Health Service (NHS).